Ecotourism Development Strategy for Local Socio-Economics: A Systematic Literature Review - Adi Septiawan; Muhamad Bai’ul Hak; Santi Nururly; Devi Oktaviana; Yudha Prayogi (Journal of Finance, Economics and Business, 2023)
The potential of ecotourism to enhance the well-being of local populations and preserve the environment is significant, as it places emphasis on both natural and cultural sustainability. The study aims to identity the development of ecotourism and their effects on the socio-economic of local communities by using Systematic Literature Review (SLR). This systematic literature review (SLR) examines the most recent research conducted in the topic under investigation. The findings of the investigation demonstrate a range of tactics employed in the development of ecotourism, encompassing product diversification, active involvement of local communities, utilization of technology for effective management, infusion of private investment, and the protection of cultural heritage. Additionally, we have observed the favorable influence of ecotourism on the financial earnings and employment opportunities of indigenous people, as well as its role in the conservation and safeguarding of local cultural heritage. Nevertheless, this systematic literature review (SLR) also sheds light on the obstacles and adverse consequences that necessitate careful consideration, including the issues of excessive tourism and socioeconomic disparities. This study offers a comprehensive analysis of the intricacies involved in the growth of ecotourism and its impact on the well-being of local populations. Additionally, it identifies potential areas for future research in the realm of sustainable ecotourism within the Indonesian environment.